Mind the gap: an analysis of core capacities of the international health regulations (2005) to respond to outbreaks in Yemen - Hanan Noman; Fekri Dureab; Iman Ahmed; Abdulwahed Al Serouri; Taha Hussein; Albrecht Jahn (BMC, 2021)
Abstract Background Yemen that has been devastated by war is facing various challenges to respond to the recent potential outbreaks and other public health emergencies due to lack of proper strategies and regulations, which are essential to public health security. The aim of this study is to assess the implementation of the International Health Regulations (IHR 2005) core capacities under the current ongoing conflict in Yemen. Methods The study simulated the World Health Organization (WHO) Joint External Evaluation (JEE) tool to assess the IHR core capacities in Yemen. Qualitative research methods were used, including desk reviews, in-depth interviews with key informants and analysis of the pooled data. Result Based on the assessment of the three main functions of the IHR framework (prevention, detection, and response), Yemen showed a demonstrated or developed capacity to detect outbreaks, but nevertheless limited or no capacity to prevent and respond to outbreaks. Conclusion This study shows that there has been poor implementation of IHR in Yemen. Therefore, urgent interventions are needed to strengthen the implementation of the IHR core capacities in Yemen. The study recommends 1) raising awareness among national and international health staff on the importance of IHR; 2) improving alignment of INGO programs with government health programs and aligning both towards better implementation of the IHR; 3) improving programmatic coordination, planning and implementation among health stakeholders; 4) increasing funding of the global health security agenda at country level; 5) using innovative approaches to analyze and address gaps in the disrupted health system, and; 6) addressing the root cause of the collapse of the health services and overall health system in Yemen by ending the protracted conflict situation.